Analysis Black Spot on Tanjungpura - Imam Bonjol Road Section Pontianak using the Accident Equivalent Number Method - Widiyani, Agnes; Kadarini, S. Nurlaily; Sumiyattinah, Sumiyattinah (Jurnal Teknik Sipil, 2025)
The increasing number of traffic accidents due to rapid population growth, inadequate road infrastructure, and low driver awareness poses a significant threat to public safety. This study aims to analyze the characteristics of traffic accidents and identify accident-prone areas (black sites) and points (black spots) along the Tanjungpura"“Imam Bonjol road corridor in Pontianak City. The research utilizes traffic accident data from 2018 to 2023, obtained from the Traffic Unit of the Pontianak City Police, and applies both the Accident Equivalent Number (AEK) and Cumulative Sum (CUSUM) methods to identify high-risk segments. The analysis revealed four accident-prone segments"”Segments 6, 7, 8, and 10"”with Segments 6 and 7 demonstrating consistent increases in accident frequency. The majority of accident victims sustained minor injuries, with incidents most frequently occurring on Saturdays and during the afternoon hours. Hit-and-run incidents and motorcycles were the most prevalent type of collision and vehicle involved, respectively. Field surveys indicated high traffic volumes and low vehicle speeds in black spot areas, along with deficiencies in road safety infrastructure such as faded markings and missing signage. The study recommends targeted interventions including road surface repairs, improved signage, and the construction of pedestrian facilities to mitigate traffic accidents and enhance road safety in identified black spot areas